Application of mixed models in sensory analysis of probiotic mango juice (Research, Society and Development, 2021)
The present work aimed to apply the mixed models to the results of the sensory analysis of probiotic mango juice with Bifidobacterium animalis ssp. Lactis - BB-12. Physicochemical analyzes (pH, titratable acidity, total solids, and color parameters), the viability of probiotics was performed, and for sensory analysis, the affective method and the acceptance test were used, where the attributes were analyzed in mango juices with and without probiotic. The encapsulated probiotic remained viable in the juice, and the physicochemical analysis showed results as expected for this type of product. In the results of the random effect of the sensorial analysis, there was a great variability of panelists for the aroma attribute, standing out as the best attribute both for mango juice with probiotics and for juice without probiotics. In the acceptance test, the panelists showed a greater preference for mango juice without probiotics, however, concerning mango juice with probiotics, the panelists liked the aroma and showed a satisfactory purchase intention. Based on the results, it can be concluded that with the use of the mixed models it was possible to estimate the variability between the panelists and their scores.